Antimicrobial Effects of Silver Nanoparticles Produced by Laser Ablation - A. Wajih, Zainab; T. Al-dahan, Ziad; Al shahwany, Ayyad (Iraqi Journal of Science, 2023)
In this article Silver nanoparticles have been synthesized through physical method where the Nd-YAG laser has been used.The antimicrobial activities of these silver nanoparticles were investigated on two types of bacteria Escherichia coli and Staphylococcus aureus. These bacteria were used as representatives of Gram-negative and Gram-positive bacteria, respectively. Two experiments have been made The first one was to test the effectiveness of silver nanoparticles as an antimicrobial agent on Gram negative bacteria Escherichia coli and Gram positive bacteria Staphylococcus aureus, while the other one (susceptibility Test) was to evaluate antimicrobial agents effective against bacteria resistant to multiple antibiotics. This study showed that Ag-NPs that synthesized by laser ablation have a great effect on S. aureus and E. coli bacteria and have potent antibacterial activities against Staphylococcus epidarmials (antibiotic-resistant) bacteria cells .